Renewable Energy in International Law: The Russian Perspective for Developing a Common BRICS Approach - A. Vylegzhanin; D. Ivanov; M. Milyukova (Publishing House V.Ема, 2023)
The growing inﬂuence of renewable energy in the economy raises concerns about the need for perfecting the relevant international legal regime so as to satisfy all the stakeholders concerned. This article analyzes the relevant legal position of Russia as one of the largest exporters of energy-related products, while focusing on cooperation in this area as the BRICS Energy Prospects. The research reveals a number of ﬁndings: Russian Energy Policy has so far cautiously supported the promotion of renewable energy internationally in the context of energy eﬃciency and energy security; nevertheless, Russia has demonstrated a very restrained approach to the development of legally binding instruments on the matter. The authors conclude that it may be viable to ﬁnd a reasonable “compromise of compromises” for the evolving international legal regime of renewable energy, and if this were to be accomplished, BRICS could assume a leading international position for the creation of such a regime.